A Multiwavelength View of the Rapidly Evolving SN 2018ivc: An Analog of SN IIb 1993J but Powered Primarily by Circumstellar Interaction - Keiichi Maeda; Poonam Chandra; Takashi J. Moriya; Andrea Reguitti; Stuart Ryder; Tomoki Matsuoka; Tomonari Michiyama; Giuliano Pignata; Daichi Hiramatsu; K. Azalee Bostroem; Esha Kundu; Hanindyo Kuncarayakti; et al. (The Astrophysical Journal)
SN 2018ivc is an unusual Type II supernova (SN II). It is a variant of SNe IIL, which might represent a transitional case between SNe IIP with a massive H-rich envelope and SNe IIb with only a small amount of the H-rich envelope. However, SN 2018ivc shows an optical light-curve evolution more complicated than that of canonical SNe IIL. In this paper, we present the results of prompt follow-up observations of SN 2018ivc with the Atacama Large Millimeter/submillimeter Array. Its synchrotron emission is similar to that of SN IIb 1993J, suggesting that it is intrinsically an SN IIb–like explosion of an He star with a modest (∼0.5–1 M _⊙ ) extended H-rich envelope. Its radio, optical, and X-ray light curves are explained primarily by the interaction between the SN ejecta and the circumstellar material (CSM); we thus suggest that it is a rare example (and the first involving the “canonical” SN IIb ejecta) for which the multiwavelength emission is powered mainly by the SN–CSM interaction. The inner CSM density, reflecting the progenitor activity in the final decade, is comparable to that of SN IIb 2013cu, which shows a flash spectral feature. The outer CSM density, and therefore the mass-loss rate in the final ∼200 yr, is higher than that of SN 1993J by a factor of ∼5. We suggest that SN 2018ivc represents a missing link between SNe IIP and SNe IIb/Ib/Ic in the binary evolution scenario.